Molecular requirements involving the human platelet protease-activated receptor-4 mechanism of activation by peptide analogues of its tethered-ligand. (17th November 2017) - Moschonas, I. C.; Kellici, T. F.; Mavromoustakos, T.; Stathopoulos, P.; Tsikaris, V.; Magafa, V.; Tzakos, A. G.; Tselepis, A. D.
Abstract: Thrombin is the most potent agonist of human platelets and its effects are primarily mediated through the protease-activated receptors (PARs)-1 and -4. Although PAR-1 has higher affinity for thrombin than PAR-4, both receptors contribute to thrombin-mediated actions on platelets. Recently, a potent and selective PAR-1 antagonist (vorapaxar) was approved for clinical use in selected patients. In contrast, despite the fact that several PAR-4 antagonists have been developed, few of them have been tested in clinical trials. The aim of the present study was to elucidate the molecular requirements involving the PAR-4 mechanism of activation by peptide analogues of its tethered-ligand. Eight synthetic PAR-4 tethered-ligand peptide analogues were synthesized and studied for their agonistic/antagonistic potency and selectivity toward human washed platelet aggregation, using light transmittance aggregometry. In addition, in silico studies were conducted to describe the receptor–peptide interactions that are developed following PAR-4 exposure to the above analogues. To provide a first structure-activity relationship rationale on the bioactivity profiles recorded for the studied analogues, molecular docking was applied in a homology model of PAR-4, derived using the crystal structure of PAR-1. The following peptide analogues were synthesized: AYPGKF-NH2 (1), GYPGKF-NH2 (2), Ac- AYPGKF-NH2 (3), trans-cinnamoyl- AYPGKF-NH2 (4), YPGKF-NH2 (5), Ac- YPGKF-NH2 (6), trans-cinnamoyl- YPGKF-NH2 (7), and caffeoyl- YPGKF-NH2 (8). Peptide (1) is a selective PAR-4 agonist inducing platelet aggregation with an IC50 value of 26.2 μM. Substitution of Ala-1 with Gly-1 resulted in peptide (2), which significantly reduces the agonistic potency of peptide (1) by 25-fold. Importantly, substitution of Ala-1 with trans-cinnamoyl- 1 resulted in peptide (7), which completely abolishes the agonistic activity of peptide (1) and renders it with a potent antagonistic activity toward peptide (1)-induced platelet aggregation. All other peptides tested were inactive. Tyr-2, residue, along with its neighboring environment was a key determinant in the PAR-4 recognition mode. When the neighboring residues to Tyr-2 provided an optimum spatial ability for the ligand to enter into the binding site of the transmembrane receptor, a biological response was propagated. These results were compared with the predicted binding poses of small molecule antagonists of PAR-4, denoted as YD-3, ML-354, and BMS-986120. π–π stacking interaction with Tyr-183 appears to be critical and common for both small molecules antagonists and the peptide trans-cinnamoyl- YPGKF-NH2 . Conclusively, the lipophilicity, size, and aromatic nature of the residue preceding Tyr-2 are determining factors on whether a human platelet PAR-4 tethered-ligand peptide analogue will exert an agonistic or antagonistic activity.